Exploring Extracurricular Clubs for Building Social Competence of Students With Autism - McDaniel, Sara L.; Hall, Laura J.; Kraemer, Bonnie K. (Frontiers in Psychiatry, 2022)
Individuals with autism experience challenges in social communication that directly impacts in-school and post-school performance. A growing number of these students are taught in general education settings in public high schools, where creating opportunities for practice of social communication skills is frequently a challenge. This exploratory, mixed methods pilot investigation explores existing and potential opportunities for high school students with autism to practice 21st century skills, including communication, in extracurricular club environments. Findings indicate that extracurricular club settings are rich environments in which all participating students, including those with autism, have opportunities to practice critical 21st century skills in a context related to their interests.